Equality and shame : The expected and feared at the party - Conlin, Sean (1974)
Although the religious phenomenon should not be explained exclusively from a sociological approach, however, the sociological explanation can help us understand it. In a certain sense, this article will be dedicated not so much to the study of religion as to its secularization, which seems to us to be a part of the expansion of the city towards the countryside and a consequence of the entry of marginal groups into the national market economy.